Effects of industrial-scale pickling processes on the dynamic changes in the physicochemical indicators and microbial diversities of Yacai - Hong-Xian Zhang; Fan-Bing Meng; Yu-Nong Zhou; Su-Qin Luo; Qiang Yang; Yun-Cheng Li; Da-Yu Liu (Food Chemistry: X, 2024)
The effects of dry-salted and salt-fermented processing on the physicochemical characteristics and microbial communities of Yacai were systematically investigated. The results showed that the contents of total acid, amino acid nitrogen (AAN) and nitrite in the final products of dry-salted Yacai were greater than those in salt-fermented Yacai. Lactic acid was the dominant organic acid in the two types of Yacai. Dry-salted processing is more conducive to forming a high-quality reddish-brown color. During whole pickling process, the microbial diversity of dry-salted Yacai was higher than that of salt-fermented Yacai, particularly in the early and middle stages of fermentation. For dry-salted Yacai, 8 bacteria (Natribacillus, Chromohalobacter, Marinococcus, Lentibacillus, Nesterenkonia, Gracilibacillus, Oceanobacillus and Tetragenococcus) and 1 fungus (Zygosaccharomyces) showed a significant positive correlation with AAN. For salt-fermented Yacai, 8 bacteria (Gracilibacillus, Alkalibacillus, Oceanobacillus, Virgibacillus, Lentibacillus, Salibacterium, Chromohalobacter and Tetragenococcus) and 3 fungi (Zygosaccharomyces, Millerozyma, and Wickerhamomyces) exhibited significant positive correlations with AAN.